Adiponectin attenuates allergen-induced airway inflammation and hyperresponsiveness in mice - Shore, Stephanie A.; Terry, Raya D.; Flynt, Lesley; Xu, Aimin; Hug, Christopher (Journal of allergy and clinical immunology, 2006)
Epidemiologic data indicate an increased incidence of asthma in the obese. Because serum levels of the insulin-sensitizing and anti-inflammatory adipokine adiponectin are reduced in obese individuals, we sought to determine whether exogenous adiponectin can attenuate allergic airway responses. We sensitized and challenged BALB/cJ mice with ovalbumin (OVA). Alzet micro-osmotic pumps were implanted in the mice to deliver continuous infusions of buffer or adiponectin (1.0 μg/g/d), which resulted in an approximate 60% increase in serum adiponectin levels. Two days later, mice were challenged with aerosolized saline or OVA once per day for 3 days. Mice were examined 24 hours after the last challenge. OVA challenge increased airway responsiveness to intravenous methacholine, bronchoalveolar lavage fluid cells, and T H2 cytokine levels. Importantly, each of these responses to OVA was reduced in adiponectin- versus buffer-treated mice. OVA challenge caused a 30% reduction in serum adiponectin levels and a corresponding decrease in adipose tissue adiponectin mRNA expression. OVA challenge also decreased pulmonary mRNA expression of each of 3 proposed adiponectin-binding proteins, adiponectin receptor 1, adiponectin receptor 2, and T-cadherin. Our results indicate that serum adiponectin is reduced during pulmonary allergic reactions and that adiponectin attenuates allergic airway inflammation and airway hyperresponsiveness in mice. The data suggest that adiponectin might play a role in the relationship between obesity and asthma.